2011
DOI: 10.1099/jmm.0.034611-0
|View full text |Cite
|
Sign up to set email alerts
|

Exotoxin gene backgrounds in bloodstream and wound Staphylococcus aureus isolates from geriatric patients attending a long-term care Spanish hospital

Abstract: The exotoxin gene content was established for 62 Staphylococcus aureus isolates causing bloodstream (n531) and wound (n531) infections in geriatric patients attending a long-term care Spanish hospital from 1996 to 2006. Content was determined based on PCR screening of genes encoding five haemolysins, three exfoliatins, three leukotoxins and 21 pyrogenic toxin superantigens (PTSAgs), in addition to markers of genomic (nSab) and pathogenicity (SaPIs) islands. Exotoxin genes were abundant in both bloodstream (11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…AD supports our thesis that AD patients get infected by potentially less virulent S. aureus strains due to their overwhelming immune response and skin barrier dysfunction whereas S. aureus strains infecting patients without skin disease require additional virulence factors to cause disease. This hypothesis is supported by the study of Argudin et al who found 98% of infecting S. aureus strains isolated from patients with skin infections in Spain carried an exfoliative toxin (eta and/or etb [29,30]. The only virulence gene more prevalent in the AD group in the present study was sea (p< 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…AD supports our thesis that AD patients get infected by potentially less virulent S. aureus strains due to their overwhelming immune response and skin barrier dysfunction whereas S. aureus strains infecting patients without skin disease require additional virulence factors to cause disease. This hypothesis is supported by the study of Argudin et al who found 98% of infecting S. aureus strains isolated from patients with skin infections in Spain carried an exfoliative toxin (eta and/or etb [29,30]. The only virulence gene more prevalent in the AD group in the present study was sea (p< 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Differences in exotoxin gene carriage between nasal and nosocomial isolates have also been reported [31,49e51]. In this study, the healthy carrier isolates from Asturias were slightly less toxigenic (4e23 exotoxin genes per isolate with an average of 14) than the nosocomial isolates from the same region, which were recovered from spontaneous suppurative infections, surgical wounds, urine, tracheobronchial aspirates, skin exudates, or blood of patients with different diseases (11e23; average of 15) [9,11]. The exfoliatin genes eta and etb, the leukotoxin genes lukED and lukPV, and the enterotoxin gene sec, were statistically more frequent in nosocomial isolates, while others (etd, sea, sed-selj-ser and seh) were more common in healthy carrier isolates ( Table 1).…”
Section: Discussionmentioning
confidence: 65%
“…The enterotoxin genes of the egc locus are usually more common among nasal than invasive isolates, and it has been proposed that the egc-encoded toxins could enhance the potential carriage of S. aureus [49,50,52]. In Asturias, however, 100% of the nosocomial isolates [9,11] and a very high percentage of the nasal isolates (88.4%) carried egc1 or egc2, with the latter being significantly more frequent in the isolates from healthy students. With a single exception, all egc2-positive isolates detected in this study were positive for sea, a combination also reported for other nasal isolates [51].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, in comparison with other hemolysin genes, hlg still remained a more prevalent hemolysin among these isolates. [ 37 38 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies showed that the acquisition of resistant genes alters secretion of virulence determinants, that means the expression of antibiotic-resistant genes reduces the expression of toxins. [ 37 38 39 ]…”
Section: Discussionmentioning
confidence: 99%